ANALISIS OPTIMALISASI BIAYA PENGIRIMAN DENGAN MENGGUNAKAN METODE LEAST COST PADA PT SINARMAS LOGISTIK INDONESIA - Firmansyah, Indra; Satria, Muhammad Rizal; Vanesa, Juli Etri (LAND JOURNAL, 2025)
PT Sinarmas Logistik Indonesia is one of the companies engaged in land transportation and services. This Final Project aims to solve the problem of optimizing the company's shipping costs using the Least Cost method, using POM QM software for shipping cost optimization calculations. The research aims to reduce shipping costs which currently reach Rp 1,093,771,999 in March 2024. The analysis results show that the application of the least cost method can reduce shipping costs to Rp 363,381,910. To validate the results, a two-sample correlated comparative hypothesis test was conducted using IBM SPSS Statistics version 27, resulting in a tcount of 6.720 and a ttable of 1.98326. Because tcount> ttable, H0 is rejected and Ha is accepted, indicating that there is a difference in the comparison of shipping costs before and after using the Least Cost method.